Information Systems Stock Inventory in CV Kencana Motor using Laravel Frame - Mukti Ali; Yulianti; Emil Riza Putra (TEPIAN, 2021)
The system for recording stock inventory at CV Kencana Motor, which is done manually, causes errors in recording stock inventory. These errors make the stock item report inaccurate with the original. This study aims to design an income information system and recording stock goods at CV Kencana Motor. The design of this system is made using Data Flow Diagram (DFD) and Contek Digram and Flowchart. The results of this study indicate, this information system built can overcome errors in the calculation of sales transactions, purchases and can overcome the inventory data collection at CV Kencana Motor. Information system at CV Kencana Motor can help in making reports and searching for data more quickly and accurately when needed.